The Green Mandate's Metrics: Examining the Influence of Political Connections, Financial Factors, and State Owned-Enterprise on Green Board Committee - Hartono, Putri Amallia; Juanda, Ahmad (Journal of Accounting Research, Organization and Economics, 2025)
Objective This study aims to examine the relationship between Political Connection, Size, Leverage, ROA, State Owned-Enterprise, and Green Board Committee.Design/Methodology This study uses a quantitative-associative method, using descriptive tests, T-tests, and multiple linear regression robustness test. The population includes all companies listed on the IDX with an ESG score in 2023. Samples are selected via purposive sampling, primarily requiring an ESG score from ESG Risk and data from Annual Report and Sustainability Reports.Results Financial factors play an important role in influencing the Green Board Committee because financial resources are an important aspect of company operations, increasing reputation, and gaining trust from stakeholders. On the other hand, non-financial variables, namely Political Connection and State-Owned-Enterprise, do not have implications for the Green Board Committee because each type of business entity, namely BUMN or Non-BUMN, will practically implement policies based on sustainability aspects to increase the company's competitive advantage and is not influenced by political solid dynamics.Novelty/Originality The implications of this research emphasize the viewpoint of Resource Dependence Theory and Institutional Theory that the role of liaison between the company and the external environment is essential to obtain resources and active participation in increasing competitiveness and market competition. This relates to the company's efforts to disclose sustainability to obtain assessments from stakeholders. The novelty of the research is that analyzing new measurements of the Green Board Committee variable by adopting a more comprehensive approach by combining several theoretical perspectives.